Herpes Simplex-1 and Toxoplasma gondii in Obsessive-Compulsive Disorder: clinical and brain imaging correlates. (1st June 2022) - Maia, A.; De Souza Queiroz, J.; Barahona-Correa, B.; Oliveira, J.; Oliveira-Maia, A.J.
Abstract : Introduction: Obsessive-compulsive disorder (OCD) is a chronic, prevalent, and highly impairing psychiatric illness. While its aetiology remains unknown, several infectious agents have been associated to obsessive-compulsive symptoms, including herpes simplex virus 1 (HSV-1) and Toxoplasma gondii. Objectives: To evaluate the serostatus for HSV-1 and Toxoplasma gondii in sample of patients with OCD, as well as its clinical and brain imaging correlates. Methods: Twenty-six patients with OCD and 30 healthy controls recruited in Lisbon were assessed for sociodemographic and clinical characteristics using the Yale-Brown Obsessive-Compulsive Scale-II (YBOCS-II) and the Beck Depression Inventory-II (BDI-II). Seropositivity for HSV-1 and Toxoplasma gondii was assessed in serum using ELISA, and volumes of cortical and subcortical structures were assessed using T1-weighted magnetic resonance imaging. Results: YBOCS-II and BDI-II scores were significantly higher in patients, while age, sex, smoking status, and seropositivity for HSV-1 and Toxoplasma gondii were similar between the two groups. Among OCD patients, those seropositive for HSV-1 had significantly lower volumes of total white-matter, total grey-matter, left and right putamen, while for HSV-1 seropositive healthy controls, only the last two were significantly smaller. In multiple regression analyses to control for age, associations between HSV-1 and brain volumes were conserved, while the effect of age was not significant. No significant differences were found in brain volumes of patients with OCD according to seropositivity for Toxoplasma gondii. Conclusions: Our preliminary results suggest that in patients with OCD, seropositivity to HSV-1 is associated with smaller volumes of total white- and grey-matter in the brain. Disclosure: No significant relationships.